Peran Bahasa Dalam Pembentukan Identitas Budaya Di Indonesia - Kevin Rewardi Harefa; Kristian Harapan Harefa (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2024)
As a medium of expression and communication that captures the rich history and culture of the country, language plays a crucial part in the development of Indonesian cultural identity. In this regard, the article "The Role of Language in Forming Cultural Identity in Indonesia" describes how language serves as a symbol of identity that unites Indonesia's diverse tribes and ethnic groups in addition to serving as a communication tool. As an official language, Indonesian is crucial to preserving the integrity and unity of the country. People from various backgrounds may communicate and comprehend one another using this language without losing their cultural identity. In addition, regional languages play a significant role in preserving cultural variety by facilitating the generational transmission of regional customs and beliefs. The difficulties facing national identity in the age of globalization, when the persistence of local values may be threatened by foreign cultural influences, are also highlighted in this article. In this instance, language serves as a tool to preserve a community's distinct identity in the face of worldwide cultural uniformity. For Indonesian society to preserve its rich and varied cultural legacy, it is imperative that people understand the role that language plays in creating and preserving cultural identity. All things considered, language plays a multifaceted and intricate function in Indonesian cultural identity formation. Language serves as the primary foundation for the richness and diversity of the country's culture, not only as a tool for communication. The Indonesian people can guarantee that their cultural identity will continue to be robust and significant in the future by working together to protect and honor the many languages that are currently spoken.